SOCIAL AND PHILOSOPHICAL ANALYSIS OF THE INTERNET AS A SOCIAL INSTITUTION IN CONDITIONS OF INFORMATION SOCIETY DEVELOPMENT - Lytovchenko, Iryna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. In conditions of the information society development we are active observers and actors of the establishment and functioning of a fundamentally new social institution – the Internet. The aim of this article is the socio-philosophical analysis of the Internet peculiarities as a social institution of information society. Research methods are sociocultural and systematic approaches in their dialectical unity, as well as structural-functional method, principles of interrelations and unity of historical and logical сognition. Research results. The scientific works of D. Bell, J. Baudrillard, M. Castells, J. Naisbitt, A. Toffler, A. Turen, F. Fukuyama, etc. deserve special attention in the comprehension of the new information reality. The scientific developments of P. Bourdieu, B. Latour, H. Blumer, J. Law, H. Garfinkel, E. Goffman are actual in studying peculiarities of Internet institutionalization. Scientific searches of A. Antypova, L. Drotianko, S. Ischuk, O. Kirnytskyi, V. Lyah, V. Onoprienko, S. Ordenov, T. Poda, I. Skyba and others are devoted to the information society peculiarities, possibilities of information and communication technologies, role of the Internet in the domestic philosophical opinion. Discussion. As a social institution the Internet plays a role as an intermediary, translator of economic, political, social, cultural, religious norms, values, behavior models of different social groups. This social institution is becoming an important component of the institutional modern society structure, which integrates, regulates and coordinates the variaty of individual human actions, regulates social relations and connections in social networks, virtual communities, interactive platforms and the entire global network in particular. The Internet has a significant influence on traditional social institutions, transforming their content, forms, functions and others. Conclusions. The development of information and communication technologies has contributed to the emergence, spread and penetration of the global Internet in all human life spheres. The rapid evolution of the Internet has caused significant changes in the structure, forms and functions of social institutions. In fact, Internet became a new social institution, which meets the urgent needs of information society members in communication, information, interaction, etc., and also organizes and regulates different social practices. The development of the Internet as a social institution is proceeding at a rather fast pace and contributes to the transformation of the system of social connections and relations, development and implementation of new social norms, rules, values, beliefs, behavior models, etc. Today the Internet has all the features of the social institution, which performs important functions, meeting the actual needs of information society members.